The construction of knowledge in Islamic civilization : Qudāma b. Jaʻfar and his Kitāb al-Kharāj wa-ṣināʻat al-kitāba - Heck, Paul L. (Leiden ; Boston : Brill, 2002)
"This study examines the role of the state in the construction of knowledge in Islamic civilization in its early classical period (third/ninth and fourth/tenth centuries). Different voices representing different social groups - savants, litterateurs, religious scholars, state officials - all brought their particular conception of knowledge to bear on the formation of the various branches of knowledge known to Islamic civilization. Reading the works of various branches of knowledge alongside the administrative encyclopedia of Qudama b. Ja'far (d.337/948), a state official in the employ of the Abbasid dynasty, has served to highlight the particular point of view of the state in the intellectual and cultural dialogue of the day. At the same time, this approach has shown Islamic civilization to be as much a dialogue of values between the different social groups of the day as a series of events or collection of ideas."--Jacket
Language And Administration -- Epistles -- The Grammatical Category -- Ibn Qutayba -- Qudama and the Grammatical Category: I -- al-Nahhas -- Qudama and the Grammatical Category: II -- The Bureaucratic Category -- al-Baghdadi -- al-Suli -- Qudama and the Bureaucratic Category -- The Linguistic Category -- Qudama and the Linguistic Category -- Qudama's Category -- Georgraphy -- The Ptolemaic Approach -- The Administrative Approach -- The Descriptive Approach -- The Literary Approach -- Fiscal Jurisprudence -- Kitaba-consciousness -- Sharia-consciousness -- Political Thought -- The Philosophical Strand -- The Administrative Strand -- Furstenspiegel.
Revision of the author's thesis (Ph. D.)--University of Chicago, 2000.
Includes bibliographical references (pages 265-275) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Qudāmah ibn Jaʻfar, -- -922?; Kitāb al-kharāj (Qudāmah ibn Jaʻfar); Qudāma Ibn-Ǧaʻfar al-Kātib al-Baġdādī; Encyclopedias and dictionaries, Arabic; Classification; Islam and state -- History -- To 1500.; Islamic civilization; Classification; classification (information handling function); FOREIGN LANGUAGE STUDY -- General; Classification; Encyclopedias and dictionaries, Arabic; Islam and state; Islamic civilization; Islam; Wetenschap; Islam; To 1500; Geistesgeschichte 800-1100.; History